PERSEPSI PUBLIK MENGENAI PENGELOLAAN LINGKUNGAN HIDUP DI KOTA SEMARANG - Indah Fitri Purwanti; Indah Susilowati (Universitas Diponegoro, 2012)
ABSTRACT The study was done in order to identify whether the level of public perception in assessing environmental management in Semarang city seen from the Pressure, State, and Response (PSR) on several indicators or object to the research of green open space (RTH), urban forests, surface water, ground water, air, and coastal (OECD, 2008, and Kenneth, 2008). It is also providing strategic advice on sustainable environmental management to be applied. It used primary and secondary data with Quoted purposive sampling. Respondent sample was taken as the city of Semarang about 110 people respondents, and 8 respondent’s key persons. Analytical methods used were mixed method with a quantitative approach used is descriptive statistics and qualitative approach is done by direct observation in the field and in-depth interviews with key persons respondents. Efforts toward improvement by the community activities in the role in environmental management, among others: (1) Reduce or restrict the use of electronic equipment, (2) Reduce or restrict the use of clean water, (3) Purchase of environmentally friendly products, (4) Recycling waste household, (5) Plant a tree in the neighborhood (reforestation), (6) Participate in managing the environment well, (7) Use of public transportation services in order to reduce pollution levels.